2004
DOI: 10.1056/nejmoa032641
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Irradiation with or without Concomitant Chemotherapy for Locally Advanced Head and Neck Cancer

Abstract: Postoperative concurrent administration of high-dose cisplatin with radiotherapy is more efficacious than radiotherapy alone in patients with locally advanced head and neck cancer and does not cause an undue number of late complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

72
2,104
14
77

Year Published

2009
2009
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 2,798 publications
(2,267 citation statements)
references
References 37 publications
72
2,104
14
77
Order By: Relevance
“…The efficacy of NAC is controversial, as described above, and no report supports NAC with a high evidence level. Accordingly, at present, the standard treatment of oral cancers is surgery alone, and radiotherapy or concomitant chemoradiotherapy after surgery is recommended for high-risk cases in which recurrence or metastasis is expected [12,37,38]. In our study, NAC increased the local recurrence rate over that in patients without NAC.…”
Section: Discussionmentioning
confidence: 47%
“…The efficacy of NAC is controversial, as described above, and no report supports NAC with a high evidence level. Accordingly, at present, the standard treatment of oral cancers is surgery alone, and radiotherapy or concomitant chemoradiotherapy after surgery is recommended for high-risk cases in which recurrence or metastasis is expected [12,37,38]. In our study, NAC increased the local recurrence rate over that in patients without NAC.…”
Section: Discussionmentioning
confidence: 47%
“…A relatively recent, prospective, randomized controlled trial conducted by the European Organization for Research and Treatment of Cancer (EORTC) suggested that intensification of therapy, not only with PORT but also with concomitant chemotherapy, is warranted with a margin <5 mm in head and neck SCC, including SCC of the oral cavity. 1,3 Another trial conducted in parallel by the US Radiation Therapy Oncology Group (RTOG) supported the role of CERT for high-risk margins, which, however, was defined as tumor at the resected margin. 2 Note that, in addition to margin status, the EORTC trial defined high risk as extracapsular extension (ECE) of lymph node disease, clinical involvement of lymph nodes There was a strong association between the number of adverse features and local control.…”
Section: Discussionmentioning
confidence: 99%
“…The prognostic significance of surgical margin for LR of head and neck cancer and oral tongue cancer has been reported [1,[14][15][16] and it was confirmed as a risk factor when \5 mm of margin status was encountered even though the patients had postoperative adjuvant therapy. Tumor thickness has been considered to correlate with cervical lymph node metastasis but there is no clear consensus of how to measure depth or thickness and also the decisive cut-off level for elective neck treatment.…”
Section: Discussionmentioning
confidence: 87%